2009
DOI: 10.1073/pnas.0809798106
|View full text |Cite
|
Sign up to set email alerts
|

Domestication and growth hormone transgenesis cause similar changes in gene expression in coho salmon ( Oncorhynchus kisutch )

Abstract: Domestication has been extensively used in agricultural animals to modify phenotypes such as growth rate. More recently, transgenesis of growth factor genes [primarily growth hormone (GH)] has also been explored as a rapid approach to accelerating performance of agricultural species. Growth rates of many fishes respond dramatically to GH gene transgenesis, whereas genetic engineering of domestic mammalian livestock has resulted in relatively modest gains. The most dramatic effects of GH transgenesis in fish ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 57 publications
13
105
0
1
Order By: Relevance
“…In addition to its essential role in the regulation of body growth and development, it can also influence reproduction, immunity, osmoregulation, and behavior (Rise et al 2006, Devlin et al 2009). In teleosts, secretion of GH is regulated by several hypothalamic factors that are influenced by the physiological state of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its essential role in the regulation of body growth and development, it can also influence reproduction, immunity, osmoregulation, and behavior (Rise et al 2006, Devlin et al 2009). In teleosts, secretion of GH is regulated by several hypothalamic factors that are influenced by the physiological state of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the differences observed were of genetic origin and that these were either the direct or indirect result of artificial selection. Finally, Devlin et al (2008) showed in coho salmon (Oncorhynchus kisutch) that domestication and growth hormone transgenesis cause similar changes in expression for genes involved in energy metabolism of carbohydrates and lipids, protein synthesis, stress and immune functions, and cellular structure.…”
mentioning
confidence: 99%
“…Beberapa faktor ini, diduga menyebabkan beberapa individu yang disisipi gen penyandi hormon pertumbuhan berukuran lebih besar dibandingkan kontrol (Devlin et al, 2009). …”
Section: Bahasanunclassified